Peran Dewan Pengawas Syariah dan Dewan Syariah Nasional Majelis Ulama Indonesia (MUI) - Riska Febrian; Danik Firdania; Sephia Zalyanti; Aprilia Rahmasari; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The sharia banking industry should be run based on sharia principles and systems. Therefore, conformity of sharia bank operations and practices with sharia is the basic foundation of sharia banking. In this case, to support its performance, the role of the Sharia Supervisory Board is required as mandated in Banking Law No. 10 of 1998. The aim of this research is to explain the role of the Supervisory Board Sharia and the National Sharia Council of the Indonesian Ulema Council using the literature study method. The research results show that DPS is responsible for ensuring that all sharia banking products and processes comply with sharia principles. The role of DPS and DSN is not only to supervise the activities of sharia financial institutions but also to play a bigger role in encouraging the growth and development of the sharia economy and finance in Indonesia.